Arabella Boxer: A Visual Feast - Lucraft, Fiona (Petits Propos Culinaires, 1992)
Arabella Boxer: A Visual Feast: Random Century, 1991: 220 pp, much colour photography by Tessa Traeger, recipe and photograph indices but no article index, £20.00.